2009
DOI: 10.1590/s0100-40422009000200030
|View full text |Cite
|
Sign up to set email alerts
|

Eletrocromatografia capilar: contextualização, estado da arte e perspectivas

Abstract: ElEtrocromatografia capilar: contExtualização, Estado da artE E pErspEctivas milena pinotti segato, césar ricardo silva e isabel cristina sales fontes Jardim* Instituto de Química, Universidade Estadual de Campinas, CP 6154, 13084-971 Campinas -SP, BrasilRecebido em 25/3/08; aceito em 21/8/08; publiado na web em 26/1/09 CAPILLARY ELECTROCHROMATOGRAPHY: CONTEXTUALIZATION, STATE-OF-THE-ART AND PERSPECTIVES. Capillary electrochromatography (CEC) is a separation technique in which the mobile phase flow is based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 81 publications
0
3
0
1
Order By: Relevance
“…Technical innovations for interfacing CE with flow and sequential injection analysis (SIA) as sampling means have been addressed in three complementary review papers 8–10. Updated insights into separation modes that are generally less common for inorganic analytes, such as MEKC 11, MEEKC 12, NACE 13, CEC 14, or based on using ionic liquids as BGE additives 15, 16, revealed that these are still limited to solve selectivity (and solubility) issues.…”
Section: Reviewsmentioning
confidence: 99%
“…Technical innovations for interfacing CE with flow and sequential injection analysis (SIA) as sampling means have been addressed in three complementary review papers 8–10. Updated insights into separation modes that are generally less common for inorganic analytes, such as MEKC 11, MEEKC 12, NACE 13, CEC 14, or based on using ionic liquids as BGE additives 15, 16, revealed that these are still limited to solve selectivity (and solubility) issues.…”
Section: Reviewsmentioning
confidence: 99%
“…CEC is an emerging and promising technique, which combines the high selectivity of HPLC and the high efficiency of CE, and has shown great potential for analyzing complex solute mixtures . Packing columns, monolithic columns, and open‐tubular columns are commonly used in CEC.…”
Section: Introductionmentioning
confidence: 99%
“…These columns present the disadvantage of a lower loading capacity due to the smaller area of the stationary phase and the unfavorable mobile phase to stationary phase volume ratio relative to particulate and monolithic columns. 17 Due to the disadvantages observed with particulate and wall-coated open-tubular columns, the development of monolithic capillary columns containing extremely porous and easily synthesized material is of great current interest. The monoliths are prepared by polymerization processes in situ in a single step that also allows the grafting of charged species into the stationary phase, fundamental for assuring the electrosmotic flow.…”
Section: Introductionmentioning
confidence: 99%